Pharmacist interventions for obesity: improving treatment adherence and patient outcomes - Jordan MA; Harmon J (Dove Medical Press, 2015)
Melanie A Jordan, Jonathan HarmonCollege of Pharmacy – Glendale, Midwestern University, Glendale, AZ, USAAbstract: Obesity is currently a worldwide pandemic, with overweight (body mass index [BMI] ≥25 kg/m2) and obesity (BMI ≥30 kg/m2) estimated at 35% and 12% of the global adult population, respectively. According to data collected from the United States National Health and Nutrition Examination Survey, approximately 68.8% of US adults are overweight or obese. Additionally, a large burden of health care costs can be attributed directly to obesity as well as multiple, potentially preventable, comorbidities such as cancer, cardiovascular disease, and diabetes. As a result, national and international organizations, such as the US Centers for Disease Control and World Health Organization, have made halting the rise of the obesity epidemic a top priority. Pharmacists, commonly considered one of the most trustworthy and accessible health care professionals, are ideally situated to provide counseling for weight and lifestyle management. This review presents examples of pharmacist-led as well as collaborative practices that have been somewhat successful in educating and monitoring patient progress in attaining weight-loss goals. Common barriers and potential solutions to administration of lifestyle counseling and monitoring programs, such as limited pharmacist time and resources, lack of expertise and/or confidence in program administration, and patient perception and awareness, are also discussed.Keywords: pharmacy, obesity, counseling, weight loss, lifestyle management